2010
DOI: 10.1159/000314273
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Hematopoietic Stem Cell Transplantation for Acute Myeloid Leukemia in First Complete Remission: A Meta-Analysis of Randomized Trials

Abstract: Background: For those patients who are not candidates for allogeneic stem cell transplantation (SCT) or who do not have an HLA-matched donor, it is unclear whether consolidation therapy with autologous SCT results in a survival benefit compared with further intensive post-remission non-myeloablative chemotherapy or no further therapy. Methods: A meta-analysis evaluating autologous SCT versus further chemotherapy or no treatment for acute myeloid leukemia (AML) in first complete remission (CR1) was completed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 44 publications
0
40
0
Order By: Relevance
“…of life compared with patients who undergo ASCT. 32 Several randomized studies 24,25,[33][34][35][36] comparing allogeneic stem cell transplantation using HLA-identical siblings after a myeloablative conditioning regimen with ASCT and chemotherapy have reported better outcomes after allogeneic transplantation, but they have also consistently shown a decreased relapse incidence after ASCT compared with conventional chemotherapy. However, to date no randomized study has demonstrated the superiority of allogeneic transplantation using an alternative donor (unrelated or cord blood) over ASCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…of life compared with patients who undergo ASCT. 32 Several randomized studies 24,25,[33][34][35][36] comparing allogeneic stem cell transplantation using HLA-identical siblings after a myeloablative conditioning regimen with ASCT and chemotherapy have reported better outcomes after allogeneic transplantation, but they have also consistently shown a decreased relapse incidence after ASCT compared with conventional chemotherapy. However, to date no randomized study has demonstrated the superiority of allogeneic transplantation using an alternative donor (unrelated or cord blood) over ASCT.…”
Section: Discussionmentioning
confidence: 99%
“…In adults with AML, historical series of ASCT from various institutions, 17 retrospective surveys from the European Group for Blood and Marrow Transplantation (EBMT) [18][19][20][21][22] and the Center for International Blood and Marrow Transplant Research, 23 and randomized trials 24,25 have revealed long-term leukemia-free survival rates of 45-55% in patients transplanted in first remission and 25-35% for those transplanted in second remission. 26 However, in contrast to the considerable experience using oral busulfan in high-dose regimens, no studies have reported outcomes using intravenous busulfan-based conditioning regimens for ASCT.…”
Section: ©2014 Ferrata Stortimentioning
confidence: 99%
“…Consequently, they are offered consolidation treatment in CR1 with either conventional chemotherapy, autologous or allogeneic transplantation [2][3][4]. Among these options, high-dose chemotherapy (HDCT) with autologous stem cell transplantation (ASCT) can be applied to consolidate CR1 in AML patients who have favorable or intermediate risk cytogenetic and molecular abnormalities [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding ASCT, retrospective studies from various centers, [22][23][24][25] the EBMT 26,27 and the Center for International Blood and Marrow Transplantation Research (CIBMTR) 28 as well as numerous randomized studies [29][30][31][32][33][34] have indicated that the long-term leukemia-free survival of AML patients autografted in CR1 is approximately 50%, whereas that for patients autografted in CR2 is approximately 30%. Results in ALL have been inferior.…”
mentioning
confidence: 99%